Genomic differentiation of big bluestem (Andropogon gerardii) along the Great Plains’ environmental gradient - Gray, Miranda M. (Kansas State University, 2012)
Big bluestem (Andropogon gerardii Vitman) is an ecologically dominant grass of the North American grasslands with precipitation-dependent productivity. However, climatic predictions for big bluestem’s dominant range in the Great Plains include increased periods of drought. The main objectives of this research were to determine the extent of neutral and non-neutral genetic differentiation and diversity among putative big bluestem ecotypes using amplified fragment length polymorphism (AFLP) markers. This is the first study of both neutral and non-neutral genetic diversity of big bluestem which also includes source populations of well-described ecotypes studied in reciprocal common gardens. A total of 378 plants were genotyped from 11 source prairies, originating from one of three ecoregions (Central Kansas, Eastern Kansas, and Illinois). Using two AFLP primer sets, 387 polymorphic markers (error rate 9.18%) were found. Un-rooted neighbor joining tree and principle-component analyses showed continuous genetic differentiation between Kansas and Illinois putative ecotypes, with genetic overlap occurring between Kansas ecotypes. Analysis of molecular variance showed high diversity within-prairie sites (80%) relative to across-prairies (11%), and across- ecoregions (9%) (p<0.001). Within-prairie genetic diversity levels were similar among ecoregions (84-92%), with the highest genetic variation maintained in Illinois prairies (92%). Population structure analyses supported K=6 genetic clusters across the environmental gradient, with Kansas prairies belonging to three main genetic groups, and Illinois prairies having largely divergent allele frequencies from Kansas prairies. Interestingly, BAYESCAN analysis of the three putative ecotypes identified eight F[subscript]ST-outlier AFLP loci under potential diversifying selection. Frequency patterns of loci under diversifying selection were further linked to geo-environmental descriptors including precipitation, temperature severity, diurnal temperature variation, prairie location, and elevation. The observed allele frequency divergence between Kansas and Illinois ecotypes suggests tallgrass restorations should consider possible maladaptation of non-local ecotypes and genetic swamping. However, high within-prairie genetic variation may help individual big bluestem populations withstand climatic variability.
Keywords: Big bluestem; Tallgrass prairie; Ecotype; Genome scan; Amplified fragment length polymorphism; Genomic differentiation; Biology (0306); Conservation Biology (0408); Genetics (0369)